Analisis Kritis Terhadap Karya Ilmiah “Pemikiran Akidah Syaikh Nāẓim al-Qubruṣī Menurut Ahli Sunnah Wal Jamaah”: Kajian Perbahasan Waḥdah al-Wujūd dan Tauhid: Critical Analysis on the Academic Thesis Entitled “The Thought of Shaykh Nāẓim al-Qubruṣī According to Ahl Al-Sunnah wa al-Jamāʿah”: A Study on the Discussion of Waḥdah al-Wujūd and Tawḥīd - Abdul Halim, Zainul Abidin; al-Akiti, Muhammad Ayman; Zulkefli, Ahmad Arif; Mohd Zawawi, Abdullah Zawawi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The Council of Sufi Orders under The State Fatwā Department of Negeri Sembilan recognizes the legitimacy of the Naqshabandiyyah ʿĀliyah Shaykh Nāẓim al-Qubrūṣī Sufi order in 2018, accordance to sufism epistimology. However, a doctorate thesis passed in 2020 entitled “The Thought of Sheikh Nāẓim al-Qubruṣī according to the Ahl al-Sunnah Wa al-Jamāʿah” claims a possibility that Shaykh Nāẓim’s belief contradicted the Ahl al-Sunnah Wa al-Jamāʿah beliefs. This was due to the use of the word “unity” found in the books of Shaykh Nāẓim, his acceptance and belief in waḥdah al-wujūd, and the connection of these two notions with pantheism. To ascertain this claim, this research re-assessed the three notions mentioned above. This study analysed each thesis paragraph that claims the existence of “unity,” waḥdah al-wujūd, and pantheism ideas. Then, this research returns to the original speech of Shaykh Nāẓim to look at the full context of the meaning. This research also applied the lexical-semantic approach and academic views. In the debate on waḥdah al-wujūd, this research compares Shaykh Nāẓim with the writings of Imam al-Junayd and Imam al-Ghazālī. It also referred to Sufi scholars’ definitions of Sufistic terms such as ittiḥād. Regarding to the issue of pantheism, this research discovered authentic sources showing that Shaykh Nāẓim rejected this view. After conducting a critical analysis of the thesis, this research roots out that accusation of supporting the idea of “unification” resulted from a lack of in-depth understanding of the “unity” word. The accusation of waḥdah al-wujūd also occurs due to the misunderstanding of maqām al-fanā’s concept. While the accusation of pantheism occurs due to the author’s ineptness to differentiate between the Sufi school and pantheism. In conclusion, the allegation that Shaykh Nāẓim holds views that contradict the Ahl al-Sunnah is an invalid claim.